2000
DOI: 10.1515/mult.2000.19.1-2.95
|View full text |Cite
|
Sign up to set email alerts
|

The sociolinguistic stratification of Hungarian in Subcarpathia

Abstract: The minority Hungarians of Subcarpathia (Ukraine) have been regarded as a linguistically homogeneous community whose Hungarian language use is affected by their contact with Russian and Ukrainian in a uniform manner. This study demonstrates that such a view cannot be upheld in the light of quantitative empirical findings, which show Subcarpathian Hungarians to be a sociolinguistically stratified group of speakers whose Hungarian language use varies in a systematic manner according to sex, age, level of educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…They are described in Csernicsko  (1998), especially pages 235 . and 256±283; see also Csernicsko  and Fenyvesi (2000). 9.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They are described in Csernicsko  (1998), especially pages 235 . and 256±283; see also Csernicsko  and Fenyvesi (2000). 9.…”
Section: Discussionmentioning
confidence: 89%
“…A similar implicational relationship was found for (2b), which was chosen as more natural by 91.3 percent of the monolingual Hungarian students in Hungary, by 86.4 percent of the bilingual students in Slovakia who study in a school with Hungarian as the medium of instruction, and by 69.4 percent of the bilingual students who study in a school with Slovak as the medium of instruction. In another study Csernicsko  and Fenyvesi (2000) have analyzed part of the data gathered for the 7-country project`The Sociolinguistics of Hungarian Outside Hungary', which I will also draw on in this paper. 5 One of the features they have studied is the choice between a standard Hungarian synthetic vs. contact-induced analytic construction as in (3) The sentence with the contact-induced phrase utaza Âst busszal`travelling by bus' was selected as the more natural by 37.8 percent of the bi-/multilingual informants in Ukraine vs. 19.6 percent of the monolingual subjects in Hungary.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Project members set out to systematically gather data in a replicable fashion, which would allow them to answer questions such as the following: (2005), and Bodó (2005). Also based on the SHOH project are papers by Beregszászi (1995Beregszászi ( /1996, Csernicskó & Fenyvesi (2000), and Kontra (1999Kontra ( , 2001Kontra ( , 2003b. Two of the six volumes are reviewed in English by Fazakas (2014), andBiró &Laihonen (2021).…”
Section: Language Shift and Revitalizationmentioning
confidence: 99%
“…The present paper is a substantially revised and updated version ofCsernicskó and Fenyvesi (2000). Thanks are due to Anikó Beregszászi, who, together with István Csernicskó, carried out most of the research reported on in this paper.…”
mentioning
confidence: 99%